Proteomics analysis of differential protein expression identifies heat shock protein 47 as a predictive marker for lymph node metastasis in patients with colorectal cancer. Issue 6 (15th March 2017) - Mori, Koichiro; Toiyama, Yuji; Otake, Kohei; Fujikawa, Hiroyuki; Saigusa, Susumu; Hiro, Junichiro; Kobayashi, Minako; Ohi, Masaki; Tanaka, Koji; Inoue, Yasuhiro; Kobayashi, Yuhko; Kobayashi, Issei; et al.
Abstract : The discovery of biomarkers to predict the potential for lymph node (LN) metastasis in patients with colorectal cancer (CRC) is essential for developing improved strategies for treating CRC. In the present study, they used isobaric tags for relative and absolute quantitation to conduct a proteomic analysis designed to identify novel biomarkers for predicting LN metastasis in patients with CRC. They identified 60 differentially expressed proteins specifically associated with LN metastasis in CRC patients and classified the molecular and functional characteristics of these proteins by bioinformatic approaches. A literature search led them to select heat shock protein 47 (HSP47) as the most suitable candidate biomarker for predicting LN metastasis. Validation analysis by immunohistochemistry showed that HSP47 expression in patients with CRC and the number of HSP47‐positive spindle cells in the tumor stroma were significantly higher compared with those in adjacent normal colonic mucosa, and the number of the latter cells increased with tumor progression. Further, the number of HSP47‐positive spindle cells in stroma was a more informative marker for identifying LN metastasis than HSP47expression. Multivariate analysis identified spindle cells that expressed elevated levels of HSP47 as an independent predictive biomarker for CRC with LN metastasis. Moreover, these cells served as an independent marker of disease‐free and overall survival of patients with CRC. Their data indicate that the number of HSP47‐positive spindle cells in the stroma of CRC may serve as a novel predictive biomarker of LN metastasis, early recurrence and poor prognosis. Abstract : What's new? Preoperative biomarkers can potentially facilitate the classification of lymph node metastases from colorectal cancer (CRC) patients. Limited sensitivity and specificity, however, prevents their use in routine screening to predict CRC spread to the lymph nodes. In an effort to discover new biomarkers, the authors of this study performed proteomic analysis using isobaric tags for relative and absolute quantification (iTRAQ). The methodology led to the identification of heat shock protein 47 (HSP47) as a novel predictor of CRC lymph node metastasis. Tumor progression, recurrence, and patient prognosis were associated specifically with the number of HSP47‐positive spindle cells in the tumor stroma.